2003
DOI: 10.1109/lcomm.2003.815644
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of MIMO systems with closely spaced antennas

Abstract: Wide-band radio channel measurements at 5.2 GHz with four transmit and four receive antennas at variable element spacing are reported, aiming to evaluate the potential of compact antenna arrays at mobile terminals. We show that, for an element spacing d<0.5. lambda (down to 0.2. lambda ), the link capacity is not smaller than that for much larger d. This is explained by the observation that mutual coupling changes the radiation patterns of closely spaced antenna elements, individually. Compact multi-antenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 6 publications
3
38
0
Order By: Relevance
“…The work [28] finds that for the spacings between 0.1λ and 0.3λ, mutual coupling provides a clear capacity benefit, while for the spacings below 0.1λ, mutual coupling degrades the capacity, compared to the array spacing of 0.5λ. The studies [29], [30] conclude that the capacity for spacings between 0.2λ ≤ D < 0.5λ is larger than that of D ≥ 0.5λ. For two-dimensional antenna arrays, the results of this paper have convincingly demonstrated that our NURA achieves a significant higher capacity than the standard URA having the same size, albeit the capacity expressions for both the URA and NURA are based on clean steering vectors.…”
Section: Further Discussionmentioning
confidence: 99%
“…The work [28] finds that for the spacings between 0.1λ and 0.3λ, mutual coupling provides a clear capacity benefit, while for the spacings below 0.1λ, mutual coupling degrades the capacity, compared to the array spacing of 0.5λ. The studies [29], [30] conclude that the capacity for spacings between 0.2λ ≤ D < 0.5λ is larger than that of D ≥ 0.5λ. For two-dimensional antenna arrays, the results of this paper have convincingly demonstrated that our NURA achieves a significant higher capacity than the standard URA having the same size, albeit the capacity expressions for both the URA and NURA are based on clean steering vectors.…”
Section: Further Discussionmentioning
confidence: 99%
“…Therefore closely spaced antennas correlate the channel fading. As a result the capacity is reduced when the antenna spacing d is less than l/2, where l is the carrier wavelength [12]. Mutual coupling between closely spaced antenna elements is also a potential problem.…”
Section: Introductionmentioning
confidence: 99%
“…a range of antenna separations) [8], [9]. Some related works, such as [10], [11] and [12], study the impact of mutual coupling on capacity without making direct comparisons with the no-coupling case.…”
mentioning
confidence: 99%